Diseño e implementación de un sistema de medición de energía eléctrica inteligente para uso doméstico. - Chamba Loaiza, José David (2014)
This final research project is focusing on hardware/software design to measure the electrical variables. That it allows to know electric consumption at home real time. The hardware is divided into five stages: The first stage is signal acquisition using voltage and current sensors. The second is signal conditioning, that is using an electronic circuit. The third stage is based on board “Arduino Mega 2560 R3”, for signal processing. The four stage is to show of measured parameters on a Touch-LCD. Finally internet communication is done through with Ethernet technology, for which this board is based on chip ethernet “Wiznet W5100”. Software design is done using the programming language open source “arduino”, some algorithms are using like: sensors calibration, phase correction, data processing, to fined electrical variables, among others. The prototype is implemented in single phase system whit a limit load 100 amperes, also it provide information about electrical energy: current, voltage, active power, real power, apparent power, power factor. Further there are three measures of energy consumption: Daily energy consumed (watts/hour), it is going to reset every day at 18:00. Monthly consumed energy is storing in a variable for accumulate the total energy, it is going to reset on specific day of each month. Furthermore electric consumption to pay for kilo-watts/hour is included. Finally it implements an option to view history of energy consumed, it allows to get information of seven days previous and seven months early, with the respective cost of consumption the said days or months.